Strategies for Optic Pathways Decompression for Extra-Axial Tumors or Intracranial Aneurysms: A Technical Note - Mattogno, Pier Paolo; Sturiale, Carmelo Lucio; Rapisarda, Alessandro; Olivi, Alessandro; Albanese, Alessio (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Different types of skull base tumors and intracranial aneurysms may lead to compression of the optic pathways. Since most of them are biologically benign conditions, the first aim of surgery is preservation of optic nerves rather than the oncologic radicality.Materials and methods Based on the progressive technical refinements coming from our institutional experience of optic nerve compression from aneurysms and extra-axial tumors, we analyzed the surgical steps to release nerves and chiasm during tumor debulking and aneurysm clipping.Results We distinguished vascular and tumor lesions according to the main direction of optic nerve compression: lateral to medial, medial to lateral, inferior to superior, and anterior to posterior. We also identified four fundamental sequential maneuvers to release the optic nerve, which are (1) falciform ligament (FL) section, (2) optic canal unroofing, (3) anterior clinoid process drilling, and (4) optic strut removal. The FL section is always recommended when a gentle manipulation of the optic nerve is required. Optic canal unroofing is suggested in case of lateral-to-medial compression (i.e., clinoid meningiomas), medial-to-lateral compression (i.e., tuberculum sellae meningiomas), and inferior-to-superior compression (i.e., suprasellar lesions). Anterior clinoidectomy and optic strut removal may be necessary in case of lateral-to-medial compression from paraclinoid aneurysms or meningiomas.Conclusions Preservation of the visual function is the main goal of surgery for tumors and aneurysms causing optic nerve compression. This mandatory principle guides the approach, the timing, and the technical strategy to release the optic nerve, and is principally based on the direction of the compression vector.
Keywords: optic nerve; optic pathways; decompression; falciform ligament; optic canal